Sol-gel derived Li+-doped poly(ε-caprolactone)/siloxane biohybrid electrolytes - Nunes, Sílvia (2006)
Electrolytes based on a poly(ε-caprolactone) (PCL)/siloxane organic/inorganic host framework doped with lithium triflate (LiCF3SO3) were synthesised through the sol-gel process. In this biohybrid matrix short PCL chains are covalently bonded via urethane linkages to the siliceous network. Samples with salt composition n (molar ratio of PCL repeat units per Li+ ion) ranging from ∞ to 0.5 were investigated. All the ormolyte materials analysed are amorphous. Xerogels with n > 0.5 are thermally stable up to about 300°C. The most conducting ormolyte of the series is that with n = 0.5 (1.6×10−7 and 3.2×10−5 Ω−1 cm−1 at 25 and 100°C, respectively). This sample is electrochemically stable between −1 and 6 V versus Li+.